PKM. PSIKOEDUKASI KESEHATAN MENTAL PADA MASYARAKAT DI DESA WISATA PINGE - I Dewa Ayu Eka Purba Dharma Tari; I Made Mahaardhika; Putu Agus Semara Putra Giri (LPPM Universitas PGRI Mahadewa Indonesia, 2021)
The covid-19 pandemic is clear evidence that the transmission of disease is so rapid that the whole world is spared from the viral outbreak while on the one hand everyone has the right to health as a rule that health isa healthy physical, mental, spiritual, and social state that makes it possible for each person to be productive socially as well as economically. Based on preliminary asesses and in pinge village get the following images of problems: 1) there are 22 members of society affected by the pandemic and the return to the village through psychological issues such as being prone to anxiety over the unprecedented conditions, confusion of nothing to do because they are accustomed to working with other people, and some people are concerned about the continued education of their children and the psychological welfare resources typically derived from local wisdom values 2) the general public is unaware of mental health issues.It needs to be psychoeducation on mental health issues to increase understanding or skill in the prevention of psychological disorders and to increase understanding for communities especially families about psychological disorders. The average pretest baseline of public mental health knowledge falls in a medium category with an average of 61%. By psychoeducation of mental health, people's understanding increased with post-test scores averaged 84%. And the conclusion reached by pinge village visitors' knowledge and understanding on mental health has been increased.